2008
DOI: 10.1002/hup.980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged‐release melatonin, zolpidem, and their combination on psychomotor functions, memory recall, and driving skills in healthy middle aged and elderly volunteers

Abstract: This study extends previous researches showing impairment of cognitive functions by zolpidem within 5 h post-administration. Further, PR-M use was not found associated with impairment of psychomotor functions, memory recall, and driving skills, and point to a pharmacodynamic interaction between melatonin and GABA-A modulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 78 publications
5
70
0
1
Order By: Relevance
“…In addition, prolonged-release melatonin use is not associated with the residual effects which are often observed following administration of benzodiazepine and other allosteric modulators of the GABA A receptor. A study of the effects of prolonged-release melatonin in healthy men and women aged 55 years and over reported that prolonged-release melatonin was not associated with impaired memory recall, driving performance or psychomotor function (Otmani et al, 2008). Along these lines, prolonged-release melatonin has been recommended as a first line therapy in older insomnia patients (Wilson et al, 2010), and a large surveillance study recently reported that following withdrawal from Circadin®, sleep quality and alertness remained improved and rebound insomnia incidence was low for older insomnia patients (Hajak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prolonged-release melatonin use is not associated with the residual effects which are often observed following administration of benzodiazepine and other allosteric modulators of the GABA A receptor. A study of the effects of prolonged-release melatonin in healthy men and women aged 55 years and over reported that prolonged-release melatonin was not associated with impaired memory recall, driving performance or psychomotor function (Otmani et al, 2008). Along these lines, prolonged-release melatonin has been recommended as a first line therapy in older insomnia patients (Wilson et al, 2010), and a large surveillance study recently reported that following withdrawal from Circadin®, sleep quality and alertness remained improved and rebound insomnia incidence was low for older insomnia patients (Hajak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Weeklong administration of zolpidem also did not signi fi cantly impair psychomotor or cognitive functioning [ 71 ] . In contrast, another study demonstrated that older subjects experience memory impairment the day following dosing with zolpidem [ 72 ] .…”
Section: Sedative-hypnotics and Anxiolyticsmentioning
confidence: 82%
“…It also appears to be an effective sleep aid in patients with dementia, reducing sleep latency and prolonging sleep duration, though long-term use may predispose to worsening affect [ 78 ] . In a randomized, crossover study comparing melatonin and zolpidem in healthy older individuals, a prolonged-release formulation of melatonin did not impact psychomotor functioning, memory, or driving skills, whereas zolpidem negatively affected all three measures [ 72 ] .…”
Section: Sedative-hypnotics and Anxiolyticsmentioning
confidence: 97%
“…Presently, nonbenzodiazepine, positive allosteric modulators of the GABA A receptor such as zolpidem (ZOL) are the most widely prescribed hypnotic medications. Although known to induce sleep, these compounds have been shown to significantly impair psychomotor and memory functions in rodents (Huang et al, 2010;Uslaner et al, 2013;Zanin et al, 2013), non-human primates (Makaron et al, 2013;Soto et al, 2013;Uslaner et al, 2013) and humans (Balkin et al, 1992;Wesensten et al, 1996Wesensten et al, , 2005Mattila et al, 1998;Mintzer and Griffiths, 1999;Verster et al, 2002;Storm et al, 2007;Otmani et al, 2008;Gunja, 2013). Such impairment can be particularly troubling when there is an urgent need for highly functional performance in the presence of drug such as with first responders, military personnel, and caregivers.…”
Section: Introductionmentioning
confidence: 99%